STATUS KETAHANAN PANGAN RUMAH TANGGA DAN POLA ASUH SEBAGAI FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA - Fabanjo, Ivonne Junita; Sulistiyani, Sulistiyani; Rahayu, Endah Sri; Mariani, Andi; Utama, Risma Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Nutritional status in toddlers is strongly influenced by food security and parenting. The prevalence of stunting in Pamekasan Regency is 42.5%, which means that the problem of stunting in Pamekasan Regency is a serious problem. The purpose of this study was to determine household food security and parenting patterns as risk factors for stunting in toddlers. This study is a quantitative analytic study with a case control research design and a sample size of 44 case respondents and 44 control respondents. The sampling technique used was proportionate stratified random sampling. Data analysis was done by univariate analysis and bivariate analysis with chi-square test. The results showed that there was a relationship between family food security (p value: 0.010) and parenting (p value: 0.000) on the incidence of stunting. It is recommended that providing education related to the fulfillment of good nutrition to pregnant and breastfeeding mothers and for mothers of toddlers needs to be done to support the process of growth and development of children during the 1000 HPK period as an effort to prevent the incidence of stunting in toddlers. In addition, efforts to increase access and affordability to food by holding regular cheap markets that can be reached by the lower middle class can be done to support the fulfillment of balanced nutrition in the family and improve household food security status.Keywords: Food Security, Parenting, Stunting.